Analysis of the COD Payment System in Buying and Selling Transactions According to Islamic Law - Sania, Gita Sania; Miftahussurur , Wildan Miftahussurur; Azizah, Nur Azizah (Aghnina : Jurnal Hukum Ekonomi Syari'ah, 2025)
This study discusses the Cash on Delivery (COD) payment system in ecommerce transactions from the perspective of Islamic law, specifically the Shafi'i School of Thought. The COD system, which is popular in Indonesia, provides advantages such as a sense of security for consumers in online transactions, despite challenges like the risk of losses for sellers. In Islamic jurisprudence, COD transactions can be analyzed through the concepts of sales contracts and the role of third parties, such as delivery services. This study employs a literature review method to identify the compatibility of the COD system with Islamic principles, such as transparency, clarity, and trustworthiness. The findings indicate that the COD system complies with Islamic law if it fulfills the conditions for a valid contract, is free from gharar (uncertainty), and adheres to principles of fairness and mutual consent. This study provides a legal foundation and practical guidance for businesses and consumers in implementing COD transactions in accordance with Islamic principles.